Reakcje pracodawców na chorobę nowotworową pracownika jako element budowania solidarności społecznej - implikacje dla edukacji obywatelskiej - Ulaniecka, Natalia (Studia Edukacyjne, 2025)
This article examines the experiences of cancer patients and employers in relation to patient-employee role conflict, with particular attention paid to forms of workplace support provided to employees with cancer. The study is based on in-depth interviews with cancer patients, employer representatives, and a trade union representative. The analysis addresses both supportive practices and negative employer responses observed during cancer treatment and throughout the return-to-work (RTW) process following periods of absence. Selected participant quotations are included to illustrate the diversity of workplace experiences among cancer patients. The findings indicate a clear need to strengthen civic education aimed at increasing awareness of employee rights, challenging stereotypes, enhancing knowledge of the social and occupational dimensions of cancer, and developing communication skills for crisis situations. Above all, the study highlights the importance of fostering prosocial attitudes and social solidarity, including within professional and organizational contexts.